Digital Economy and the Open Source - Ambareva, Hristina (Research Papers, 2020)
The main question of the article is how the free and open-source software movement (FOSS/FLOSS) got established and strengthened in the market environment. In the second half of the 20th century, the concept of a free product on the market was very revolutionary and contradictory to the capitalist economy logic. The article consists of three parts. In the first one, counterculture is presented as a base, which gives the first and grounding level of sustainability to the free software movement. In the second one, the role of licenses and foundations to institutionalize the idea of free software and open source and to build trust in it is discussed. The third part comments on the question of whether free and open-source software movement has an anti-capitalist meaning.